Digestive capabilities of sheep, goats, cattle, and camels - Migongo-Bake, W.; Child, R.D.; Whittington, D.L. (Winrock International, 1986)
Reports on a study conducted to compare the digestive capability of sheep, goats, cattle and camels for a given forage species. Shows how the rumen digestive power would be different between the green and dry seasons by using the nylon bug technique.